Living standards, poverty and inequality in the UK: 2023 - Sam Ray-Chaudhuri; Tom Waters; Thomas Wernham; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2023)
We investigate how living standards have changed for different groups in the UK, with a particular focus on the cost of living payments and housing.
Keywords: 330; Consumption and prices; Employment and income; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Consumer behaviour; COVID-19; Distributional effects; Housing; Inequality; Living standards